Character-defining elements of shophouses buildings in Taiping, Perak - Azmi, Nur Farhana; Shamsul Harumain, Yong adilah; Ali, Azlan Shah; Zaini, Siti Farrah; Abdullah, Muhammad Faris (Faculty of Built Environment, University of Malaya, 2017)
The quality of cultural resources in influencing the distinctiveness of a place is rooted in its tangible and intangible features or collectively known as character-defining elements. While it is undeniable that a place is noticeable and regarded as meaningful due to its cultural heritage values, it is important to know where these significances lie or reside in, along with its current importance to the local community. Nevertheless, there is no single definitive list of the elements that is made available to date. Therefore, this research attempts to explore the key features of a place that can contribute to the unique character of a town and substantially drive the subsequent conservation process. A questionnaire survey was conducted in Taiping, a small town in the state of Perak to identify the key elements that define the overall value of a place, particularly shophouses buildings. Tangible and intangible features were identified as the character-defining elements of shophouses that are worthy of being preserved and maintained. The paper concludes to an interesting result where an intangible character-defining element is the most important feature that characterised the shophouses in the town.